Beautiful bad - Ward, Annie Nigh, 1970- (Toronto, Ontario, Canada : Park Row Books, 2019)
Starting a therapeutic journal in the aftermath of a scarring accident, former travel writer Maddie is forced to reckon with her husband's PTSD, her son's safety, and her family's complicated history with her best friend, Jo.
Keywords: Suspense fiction; Suspense fiction; Psychological fiction